(untitled) (Prithvi Journal of Research and Innovation, 2022)
Though lichen is an important biological entity, it has been overlooked in biodiversity assessment, research and priorities. To minimize this gap with the available resources and facilities, an initiation has been taken to enumerate the available lichen species in the premises of Prithvi Narayan Campus (PNC), Pokhara, Nepal. A survey has been conducted to explore mostly the foliose lichens diversity in 2022 and resulted 17 confirmed species belonging to 12 genera from 5 families. The Parmeliaceae and Physciaceae are found to be dominated families. Though the findings of this study are based on the morphological features, using available laboratory facilities at PNC, further in-depth survey and advanced identification methodologies are recommended.